2022
DOI: 10.1039/d1nj04204a
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the structural defects and the combined acidity of H3PW12O40/Zr-MCM-41 catalysts in ultralow sulfur diesel production

Abstract: The oxidative desulfurization (ODS) has been become an important technical route for the production of ultralow sulfur fuel. This work focused on the deep understanding the roles of structural defects,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…41,42 Many researchers have reported ODS reactions catalyzed by HPW. 43,44 De Luna and co-workers investigated the ODS rate of DBT using HPW as a catalyst and H 2 O 2 as an oxidant; the system can reach a high sulfur conversion (100.0%) at 60 1C after 40 min. 45 Wan's group studied ODS activities of BT and DBT using POMs/H 2 O 2 systems and a phase-transfer agent with the assistance of vigorous mixing and ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…41,42 Many researchers have reported ODS reactions catalyzed by HPW. 43,44 De Luna and co-workers investigated the ODS rate of DBT using HPW as a catalyst and H 2 O 2 as an oxidant; the system can reach a high sulfur conversion (100.0%) at 60 1C after 40 min. 45 Wan's group studied ODS activities of BT and DBT using POMs/H 2 O 2 systems and a phase-transfer agent with the assistance of vigorous mixing and ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…15. It has been reported that the combination of B and L acid sites benefits the oxygen transfer and sulfur oxidation in the H 3 PW 12 O 40 /Zr-MCM-41 catalysts, 29 where some B acid sites are located near L acid sites as neighbors or as adjacent combined B–L acid site pairs. Because DBT adsorption and peroxometallic and superoxometallic species formation occur on the Lewis acid centers, only in the case when a B acid site is located near this L acid site, can they participate in the ODS reaction.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that heteropolyacids containing Mo or W with lacunary Keggin units are effective for the ODS reaction, due to their strong acidic properties and tunable redox properties. 15,28,29 When heteropolyacids are mixed with an oxidant such as hydrogen peroxide, they can be transformed into polyoxometalates, which are very active for the oxidation of many organic compounds. [28][29][30][31][32] The drawbacks of heteropolyacids include a low surface area (o5 m 2 g À1 ) and low accessibility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation